First Display of Haloalkane Dehalogenase LinB on the Surface of Bacillus subtilis Spore - Wang, Fuli; Liu, Xiujie; Song, Tianyu; Pei, Chengxin; Huang, Qibin; Jiang, Hui; Xi, Hailing (Protein and Peptide Letters, 2023)
Background: LinB, as a Haloalkane dehalogenase, has good catalytic activity for many highly toxic and recalcitrant compounds, and can realize the elimination of chemical weapons HD in a green non-toxic mode.Objectives: In order to display Haloalkane dehalogenase LinB on the surface of Bacillus subtilis spore.Methods: We have constituted the B. subtilis spore surface display system of halogenated alkanes dehalogenase LinB by gene recombination.Results: Data revealed that LinB can display on spore surface successfully. The hydrolyzing HD analogue 2-chloroethyl ethylsulfide (2-CEES) activity of displayed LinB spores was 4.30±0.09 U/mL, and its specific activity was 0.78±0.03U/mg. Meanwhile, LinB spores showed a stronger stress resistance activity on 2-CEES than free LinB. This study obtained B. subtilis spores of LinB (phingobium japonicum UT26) with enzyme activity that was not reported before.Conclusion: Spore surface display technology uses resistance spore as the carrier to guarantee LinB activity, enhances its stability, and reduces the production cost, thus expanding the range of its application.
Keywords: Haloalkane dehalogenase LinB